2010
DOI: 10.1101/gad.568810
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 establishes a glutathione-mediated gradient of UVB cytoprotection in the epidermis

Abstract: Ultraviolet (UV) B irradiation can severely damage the skin and even induce tumorigenesis. It exerts its effects by direct DNA modification and by formation of reactive oxygen species (ROS). We developed a strategy to genetically activate target gene expression of the transcription factor NF-E2-related factor 2 (Nrf2) in keratinocytes in vivo based on expression of a constitutively active Nrf2 mutant. Activation of Nrf2 target genes strongly reduced UVB cytotoxicity through enhancement of ROS detoxification. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
169
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 148 publications
(171 citation statements)
references
References 56 publications
2
169
0
Order By: Relevance
“…These are of major medical importance, because Nrf2 activation is considered a powerful strategy for protection of different tissues and organs from various insults and, in particular, for cancer prevention; however, evidence is emerging that activation of Nrf2 also has negative consequences. For example, genetic or pharmacological activation of Nrf2 in keratinocytes caused skin inflammation, hyperkeratosis, and sebaceous gland enlargement (4,5). Furthermore, various NRF2-activating compounds are skin sensitizers (22,23), and recent studies suggest that Nrf2 can promote atherosclerosis in mice (24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These are of major medical importance, because Nrf2 activation is considered a powerful strategy for protection of different tissues and organs from various insults and, in particular, for cancer prevention; however, evidence is emerging that activation of Nrf2 also has negative consequences. For example, genetic or pharmacological activation of Nrf2 in keratinocytes caused skin inflammation, hyperkeratosis, and sebaceous gland enlargement (4,5). Furthermore, various NRF2-activating compounds are skin sensitizers (22,23), and recent studies suggest that Nrf2 can promote atherosclerosis in mice (24).…”
Section: Discussionmentioning
confidence: 99%
“…This causes enhanced drug resistance, increased survival under stress conditions, and hyperproliferation of the tumor cells as a result of an increased abundance of multidrug-resistance proteins, ROSdetoxifying enzymes, and metabolic enzymes (2,3). Recent studies from our laboratory also demonstrated that chronic activation of Nrf2 in keratinocytes causes hyperkeratosis, epidermal thickening due to keratinocyte hyperproliferation, cutaneous inflammation, and sebocyte hyperplasia (4)(5)(6). Therefore, we searched for soluble mediators that are controlled by Nrf2 and may affect cell proliferation and/or inflammation.…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Studies in human and mouse have shown that the proliferating basal cells of the IFE are more sensitive to UV irradiation compared with the more differentiated suprabasal cells (reviewed in Blanpain et al 2011). Upon UV irradiation the IFE basal cells exhibit sustained p53 accumulation and higher apoptosis rates, concomitant with an inverse gradient of Nrf2 expression, which controls the expression of oxidative stress regulators (Schafer et al 2010). Ex vivo studies of human epidermal SCs have shown that they are more resistant to ionizing radiation, possibly because of an autocrine/paracrine FGF2-mediated increase in DNA repair activity (Rachidi et al 2007;Harfouche et al 2010).…”
Section: Genomic Maintenance In Epidermal Stem Cellsmentioning
confidence: 99%